Analysis of the Impact of Environmental Temperature and Humidity on Cotton Fiber Quality During Initial Processing - Yaosheng Zhu; Jianhao Zhang; Xudong Zhao; Hong Xu (Journal of Natural Fibers)
This study examines the impact of temperature and humidity on cotton fiber quality during initial processing. Conducted in a Xinjiang cotton ginning mill, we used the USTER HVI1000 to analyze five quality indices: upper half mean length, uniformity, short fiber index, tensile strength, and elongation. Results indicated that temperatures below 13°C increased fiber brittleness, moisture, and significantly reduced length and strength. Optimal conditions were observed at temperatures between 13°C to 20°C with normal humidity, where length and strength were maintained. Above 20°C, the dry environment led to a decrease in these indices. While higher temperatures and lower humidity helped remove impurities and lessen cotton knots, relative humidity below 45% increased static electricity and knots. Despite data limitations, this study moves towards identifying optimal temperature and humidity levels for improving cotton quality during initial processing, providing a theoretical foundation for future enhancements.